2020
DOI: 10.1103/physrevlett.124.053402
|View full text |Cite
|
Sign up to set email alerts
|

Optical Traps for Sympathetic Cooling of Ions with Ultracold Neutral Atoms

Abstract: We report the trapping of ultracold neutral Rb atoms and Ba + ions in a common optical potential in absence of any radiofrequency (RF) fields. We prepare Ba + at 370 µK and demonstrate efficient sympathetic cooling by 100 µK after one collision. Our approach is currently limited by the Rb density and related three-body losses, but it overcomes the fundamental limitation in RF traps set by RF-driven, micromotion-induced heating. It is applicable to a wide range of ion-atom species, and may enable novel ultracol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…These systems are of particular interest to study charged impurity physics in a quantum bath. The well-controlled ionic impurities may be used to probe properties of the atomic bath, or to study the decoherence of internal states and motion while interacting with a quantum environment [4,[9][10][11][12][13][14][15]. Notably, the charge-dipole interactions are longer ranged than those found in neutral systems [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are of particular interest to study charged impurity physics in a quantum bath. The well-controlled ionic impurities may be used to probe properties of the atomic bath, or to study the decoherence of internal states and motion while interacting with a quantum environment [4,[9][10][11][12][13][14][15]. Notably, the charge-dipole interactions are longer ranged than those found in neutral systems [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…We next perform an experimental investigation of parametric driving as a tool for removing ions from a Paul trap. Our experimental setup [8,39,40] shown in Fig. 4 consists of a linear segmented Paul trap (with ion-electrode distance of 9 mm) under ultra-high vacuum (UHV).…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…octupolar) instability [28,29]. This method may be applicable to chemistry experiments which study reactions of ions and a (neutral) atomic ensemble [8,[30][31][32][33], but also to precision measurements where the spectroscopy ions are sympathetically cooled by an ion species amenable to laser cooling [34][35][36][37]. It could be extended to ions in Penning traps or storage rings.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting parameters such as induced interactions can reach a fraction of the characteristic energy E , meaning that observation of interesting quantum phases will require cooling the system to nanokelvin temperatures. Recent experimental advancements [54][55][56] indicate that this can be achieved in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In the most standard state-of-the-art setting utilizing radio-frequency ion traps, a small atom-to-ion mass ratio (e.g., lithium atoms and ytterbium ions) enables one to reach the s-wave collision energy [54]. Successful sympathetic cooling of the ion has also been reported in optical traps [55]. Furthermore, it has been shown that sub-microkelvin temperatures can be attained when ionizing a Rydberg atom inside a Bose-Einstein condensate [56].…”
mentioning
confidence: 99%